Suck It Up and Die - Meehl, Brian, author 644290 (New York, NY : Ember, 2012)
Nearly two years after Suck It Up, all Morning McCobb wants is to complete his training at the NY Fire Academy and to stay head over heels in love with Portia for as long as the chronology-crossed lovers can, given that she's now eighteen and he's stalled at sixteen. It's nearly the first anniversary of American Out Day, the historic day on which the Leaguer vampires of America began going mainstream without going bloodstream on their fellow mortal citizens. The tension between Morning's wish for a simple, out of the spotlight life, and Portia's cinematic obsession with historic events escalates to the breaking point when a super-sinister vampire rises from the grave with a powerful thirst, for revenge.